Radar micro-Doppler signatures processing and applications - Chen, Victor C.; Tahmoush, David; Miceli, William J. (The Institution of Engineering and Technology, 2014)
In this book, the authors review the current progress, challenges, and perspectives on radar micro-Doppler research and, then, introduce the phenomenology of radar micro-Doppler signatures. The following chapters include progresses in combined micro-range and micro-Doppler signature analysis, human movement analysis using a super-high resolution radar, micro-Doppler signatures in through-wall radar, identification of human movements, micro-Doppler signature of helicopter rotor blades, micro-Doppler signature of small boats in sea clutter, bistatic/multistatic micro-Doppler signatures, decomposition of micro-Doppler signatures, micro-Doppler signatures in sonar, and micro-Doppler signatures of wind turbines.